Timing of oxytocin administration to prevent post-partum hemorrhage in women delivered by cesarean section: A systematic review and metanalysis. - Maria Regina Torloni; Monica Siaulys; Rachel Riera; Ana Luiza Cabrera Martimbianco; Rafael Leite Pacheco; Carolina de Oliveira Cruz Latorraca; Mariana Widmer; Ana Pilar Betrán (PLoS ONE)
Background There is no consensus on the best timing for prophylactic oxytocin administration during cesarean section (CS) to prevent post-partum hemorrhage (PPH). Objectives Assess the effects of administrating prophylactic oxytocin at different times during CS. Methods We searched nine databases to identify relevant randomized controlled trials (RCT). We pooled results and calculated average risk ratios (RR), mean differences (MD), and 95% confidence intervals (CI). We used GRADE to assess the overall evidence certainty. Results We screened 13,389 references and included four trials. We found no statistically significant differences between oxytocin given before versus after fetal delivery on PPH (RR 0.60, 95%CI 0.15-2.47; 1 RCT, N = 300) or nausea/vomiting (RR 1.21, 95%CI 0.69-2.13; 1 RCT, N = 300). There was a significant reduction in the need for additional uterotonics when oxytocin was given immediately before uterine incision versus after fetal delivery (RR 0.37, 95%CI 0.18-0.73; I2 = 0%; 2 RCTs; N = 301). Oxytocin given before fetal delivery significantly reduced intra-operative blood loss (MD -146.77mL, 95%CI -168.10 to -125.43; I2 = 0%; 3 RCTs, N = 601) but did not change the incidence of blood transfusion (RR 0.50, 95%CI 0.13-1.95; I2 = 0%; 2 RCTs, N = 301) or hysterectomy (RR 3.00; 95%CI 0.12-72.77; I2 = 0%; 2 RCTs, N = 301). One trial (N = 100) compared prophylactic oxytocin before versus after placental separation and found no significant differences on PPH, additional uterotonics, or nausea/vomiting. Conclusions In women having pre-labor CS, there is limited evidence indicating no significant differences between prophylactic oxytocin given before versus after fetal delivery on PPH, nausea/vomiting, blood transfusion, or hysterectomy. Earlier oxytocin administration may reduce the volume of blood loss and need for additional uterotonics. There is very limited evidence suggesting no significant differences between prophylactic oxytocin given before versus after placental separation on PPH, need for additional uterotonic, or nausea/vomiting. The overall certainty of the evidence was mostly low or very low due to imprecision. Protocol: CRD42020186797.